Protein-energy supplementation for lambs: feed intake, ingestive behavior, rumen parameters and nutrient digestibility - Silva, Pâmila Carolini Gonçalves da; Ítavo, Camila Celeste Brandão Ferreira; Ítavo, Luís Carlos Vinhas; Morais, Maria da Graça; Silva, Jonilson Araújo da; Heimbach, Natália da Silva; Melo, Gleice Kelli Ayardes de; Costa, Marlova Cristina Mioto da (Semina: Ciências Agrárias, 2017)
The study evaluated the effects of dietary protein-energy supplementation on feed intake, ingestive behavior, rumen parameters and nutrient digestibility in lambs. Four castrated lambs with 31.9 kg mean body weight and fistulated rumen were tested. distributed into latin square design (4x4), four treatments were tested over four periods of time: no supplementation (control) or with supplementation at 8, 16 and 24 g kg-1 body weight. The supplement (soybean meal, soybean hulls, ground corn and minerals) was provided with roughage (Tifton Bermudagrass, Cynodon spp., hay), which was offered ad libitum once a day, at 8h00. In treatments receiving 0 (control), 8, 16 and 24 g kg-1 supplementation, dry matter intake was 685.26, 742.86, 842.51 and 1013.33 g day-1, crude protein intake was 80.18, 95.98, 118.64, 150.14 g day-1 and metabolizable energy intake 1.55, 1.91, 2.31 and 2.98 g day-1, respectively. Treatments receiving the highest supplementation levels spent less time with rumination and feeding and rested for longer (P < 0.05). Protein-energy supplementation level did not affect rumen parameters. Average rumen pH was 6.3 and rumen ammonia nitrogen 165 mg dL-1; both were affected by sampling time. Supplementation levels until 24 g kg-1 BW improves feed intake and nutrient digestibility linearly and changes ingestive behavior, lowering rumination time without affecting rumen parameters.